2007
DOI: 10.1017/s0029665107005587
|View full text |Cite
|
Sign up to set email alerts
|

Signals generating anorexia during acute illness

Abstract: Anorexia is part of the body's acute-phase response to illness. Microbial products such as lipopolysaccharides (LPS), which are also commonly used to model acute illness, trigger the acute-phase response and cause anorexia mainly through pro-inflammatory cytokines. LPS stimulate cytokine production through the cell-surface structural molecule CD14 and toll-like receptor-4. Cytokines ultimately change neural activity in brain areas controlling food intake and energy balance. The blood-brain barrier endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 121 publications
1
48
0
1
Order By: Relevance
“…[4][5][6] It is well known that cytokines are able to inhibit appetite both in healthy conditions and in various diseases (cancer, sepsis, cardiac cachexia, chronic obstructive pulmonary disease). [18][19][20][21][22] Thus, it may be questioned why, in this study, the IL-6 levels of patients who had only anorexia did not differ from those of patients who complained fatigue alone or of patients who were both not-anorexic and fatigued. The answer to this question is difficult but some considerations may be helpful: (1) in a recent study we found a trend toward higher levels of CRP in patients with poor or very poor appetite with respect to patients with very good or good appetite, although the differences were not statistically significant; 8 (2) in this study, the median IL-6 levels in patients without anorexia and fatigue, with anorexia alone, and with fatigue alone were particularly low (all below 3 pg/mL); (3) our patients, unlike those of other studies, 4,5 received a Mediterranean diet and this may have contributed to low levels of IL-6;…”
Section: Discussionmentioning
confidence: 54%
“…[4][5][6] It is well known that cytokines are able to inhibit appetite both in healthy conditions and in various diseases (cancer, sepsis, cardiac cachexia, chronic obstructive pulmonary disease). [18][19][20][21][22] Thus, it may be questioned why, in this study, the IL-6 levels of patients who had only anorexia did not differ from those of patients who complained fatigue alone or of patients who were both not-anorexic and fatigued. The answer to this question is difficult but some considerations may be helpful: (1) in a recent study we found a trend toward higher levels of CRP in patients with poor or very poor appetite with respect to patients with very good or good appetite, although the differences were not statistically significant; 8 (2) in this study, the median IL-6 levels in patients without anorexia and fatigue, with anorexia alone, and with fatigue alone were particularly low (all below 3 pg/mL); (3) our patients, unlike those of other studies, 4,5 received a Mediterranean diet and this may have contributed to low levels of IL-6;…”
Section: Discussionmentioning
confidence: 54%
“…Like PPG neurons, serotonin neurons have been shown to be involved in the regulation of food intake (30,51), and both cell populations are activated by visceral malaise (48,52,80). Similarly, both cell populations have been implicated in thermoregulation (34,70).…”
Section: Medullary Projections Of Ppg Neuronsmentioning
confidence: 99%
“…Their neurons possess various membrane receptors for injuryassociated molecules such as cytokines, eicosanoids, and adenosine triphosphate. [12][13][14][15] They send partially overlapping axonal projections to the entire gray matter of forebrain and diencephalon, as well as many brainstem regions. 16,17 Serotonin, in addition to being a classic neurotransmitter, is known from an extensive literature to have positive developmental, neuroprotective, and regenerative effects.…”
Section: Introductionmentioning
confidence: 99%